Indian Rattans (Canes): Diversity, Distribution and Propagation - Biswas, S.A.S.; Dayal, Ramesh (Indian Forester, 1995)
Rattan (Cane) is most important non-wood forest produce after timber. Its importance in socio-economic development has increased in recent past. The rattan industry has become a labour intensive and rural or forest-based with an increasing prospect for earning foreign exchange. About half a million people are directly employed in harvesting and processing of rattans in the countries of South-east Asia. The demand for better quality rattan is increasing in the trade of this species. The current trade in rattans is a multimillion dollar business. Indian cane furniture industries produce materials worth Rs. 50 million with the value of exports being Rs. 5 million. The States of Assam, Arunachal Pradesh, Andaman and Nicobar Islands, Karnataka and Kerala are the main suppliers of unprocessed rattans. Indian rattan products are exported to the countries such as Germany, Kenya, Italy, U.S.A., Sri Lanka, Bangladesh, Nepal, etc. India is endowed with ca 70 species of rattans distributed among four genera, namely Calamus, Daemonorops, Korthalsia and Plectocomia. North-eastern region can be referred as the centre of genetic diversity for the genus Calamus with ca 25 species. many of the endemic species such as Calamus inermis, C. diiaceratus, Korthalsia rogersii, etc.are under severe threat due to destruction of their habitat and over exploitation. Commercially important Indian species of rattans along with their characteristic features and uses have been elucidated in the paper. Propagation of Indian rattans by seed, wildlings, suckers, cuttings and tissue culture have been discussed. Priorities for research on Indian rattans with emphasis on the conservation measures, socio-economic and utilization aspects have been proposed.